"von dem einigen mitler Jhesu Christo". Was man von Andreas Osianders Häresie noch lernen könnte - Sparn, Walter Helmuth (Neue Zeitschrift für Systematische Theologie und Religionsphilosophie, 2022)
The first part of this contribution is devoted to my recollection of Christoph Schwöbel; both of us were pupils of Carl Heinz Ratschow, albeit at different times and in different roles. However, we both have been following a twofold counsel of our teacher, first not to restrict theology to value judgments but to strive for an ontology of Christian belief and second to work with a "Trinitarian definition of Christology". Part two recounts the turmoil around Andreas Osiander in a turbulent time of a crisis of authority around 1550. He was in the end judged to be heretic and was excluded from "true"Lutheranism in the Formula of Concord 1577. Indeed, his doctrine of justification, influenced by humanistic Neoplatonism and even the Kabbala was contrary to the predominant position of the Wittenberg school. However, the crucial point was Osiander's constellation of Soteriology, Christology and Trinitarian concept of God on a strictly exegetic basis. Part three offers a sketch of the interrelation of Osiander's soteriological model of the believer's ascension to God, his Christology of a mediator, and his concept of the divine Logos. In his time, Osiander in a way fulfilled Ratschow's twofold counsel, in opposition to Christological functionalism and theological positivism. Even today, in view of the ecumenical debate on the doctrine of justification, his thought might give useful hints for revising the aforementioned tasks in fundamental theology.
CRIS-Team Scopus Importer:2022-12-23
Keywords: Andreas Osiander Johannes Brenz; Carl Heinz Ratschow; Christology; Doctrine of Justification; Doctrine of the Trinity; Kabbala; Logos-Theology; Metaphysics; Neoplatonism